Convertible Debt: Corporate Call Policy and Voluntary Conversion - ASQUITH, PAUL; MULLINS, DAVID W. (Journal of Finance, 1991)
ABSTRACT This paper examines why, in contrast to the predictions of finance theory, firms do not call convertible debt when the conversion price exceeds the call price. The empirical results suggest that the principal reason is because some firms enjoy an advantage of paying less in after‐tax interest than they would pay in dividends were the bond converted. This cash flow incentive is the inverse of an investor's incentive to convert voluntarily if the converted dividends are greater than the bond's coupon. Because of taxation, however, the decisions by investors and firms are not symmetric, and there exist bonds which the firm may not call and an investor will not convert. The results also find that voluntary conversion is significantly related to both the conversion price and the differential between the coupon and the dividends on the converted stock.